The Nicoya segment of Middle American Trench: an Excellent Target for Drilling and Monitoring the Shallow Portion of the Seismogenic Zone - Protti, Marino (2011)
Presented before the XXV IUGG General Assembly, Melbourne, Australia, June 28-July 7, 2011.